An MRI compatible band GAP dependent fiber optic temperature sensor - Deniz, Ahmet. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
Fiber optic sensors (FOTSs) have been a research topic over two decades. Many sensor types were developed in diﬀerent schemes. Among many other parameters like pressure, location, PH level detection..etc, which can be measured by ﬁber optic sensors, temperature sensor is one of the most important, widely used and studied sensor in many ﬁelds such as medical applications like minimally invasive surgeries, In-Situ Thermal Remediation (ISTR) and oil and gas production and transportation. The objective of this thesis is to research transmittance and reﬂectance depen dence with the temperature in order to help developing a ﬁber optic microsystem temperature sensor based on the concept of the band gap energy of a gallium arsenide (GaAs) to give information to the non-invasive medical instruments under the magnetic resonance imaging (MRI). Fiber optic sensor has immunity to electromagnetic (EM) interference which is one of the best reasons to use it under the MRI. Among other semiconductors, GaAs is one of the most convenient material due to the its direct band gap . Direct band gap provides direct transitions of electrons from valence band to conduction band due to valence band and conduction band are in the same crystal momentum. So, electrons does not require an extra energy to conservation of their momentum, this provides good absorption and emission of light. Based on the properties of the GaAs, temperature changes can be monitored with a insigniﬁcant delay and error. Temperature sensing is based on the reﬂectance, transmittance and absorbance changes in the semiconductor with respect to temperature. Incident light at carefully determined wavelength will be reﬂected and transmitted with the diﬀerent intensities and correspondingly diﬀerent powers at every diﬀerent temperature. Light transmis sion and reﬂection through the GaAs crystal is also wavelength dependent. In this thesis, transmitted light power will be measured by photodetector under
Keywords: Optical fiber detectors.; Magnetic resonance imaging.; Gallium arsenide semiconductors.